Women, Men, Work and Family in Europe
XVI, 272 p.
Keywords: Social changes including an increase in dual-earner families, declining fertility, and growing problems of work-life 'balance' are underway as more women, particularly mothers, enter and remain in paid employment. The authors explore this in a number of European countries (Britain, France, The Netherlands, Finland, Norway, Sweden and Portugal). .